Assessment of impact of the rheological parameters change on sensitivity of the asphalt strain based on the test results = Ocena wpływu zmiany parametrów reologicznych na wrażliwość deformacji mieszanek mineralno-asfaltowych na podstawie wyników badań - Kurpiel, Artur; Wysokowski, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The creep test under the static loading, that allows to determine rheological properties of asphalt based on the creep curve, is the most effective test nowadays. Applied loads are non-destructive and allow to observe the course of the strain after the test load.
Keywords: parametry reologiczne; modele reologiczne; pełzanie; obciążenia statyczne; mieszanka mineralno-asfaltowa; deformacje; rheological parameters; rheological models; creep; test creep; static load; asphalt mixture; deformation